First report of chimerism in the Mediterranean red coral (Corallium rubrum) - GIORDANO, BRUNA; BRAMANTI, LORENZO (Mediterranean Marine Science, 2021)
The phenomenon of chimerism in the Mediterranean red coral (Corallium rubrum) is reported and quantified in semi-natural conditions. 1688 larvae were maintained in closed circuit in presence of a suitable settlement surface (marble tiles). Post settlement survival and chimera formation were monitored for 1 year. According to our observation, when polyps settle at close contact, a high frequency of chimerism is observed (32%). After 1 year, only 33% of chimeric individuals survived but they are 40% bigger than not chimeric ones, suggesting that chimerism could confer a competitive advantage linked to increased growth rate.